CHINA’S GEO-ECONOMIC POLICY TOWARDS CENTRAL ASIA (2014-2020) (Khairulummah, 2023)
International politics are largely determined by geo-economic factors, particularly, in the post-Cold War era. The pursuit of divergent geo-economic-cum-political interests has led to competition and conflict among a number of states, where states are exercising power through economic means. Geo-economics strategy offers states a new way - in contrast with territory-based geopolitics - of conducting power politics by exploiting the inherent asymmetric vulnerabilities of these economic interconnections. Similarly, China through its increasing financial leverage is cultivating closer diplomatic relations with nations around the world. where institutions such as the Asian Infrastructure Investment Bank and the Belt and Road Initiative are playing a big part. Following the same footings, over the last decade the relationship between China and the Central Asian Republics has undergone remarkable changes. Following its geo-economic interests and availability of space for investment in CARS, China has undeniably become a major player in Central Asia. This study focused on Chinese’s Geo-economics policy towards CARS because China is consider Central Asia as an important source of energy resources, a promising market for goods, a transportation hub for Eurasia, and an area that will contribute to its national security and development as a global leader. The study used the theoretical framework of Complex Interdependence. Moreover, the research methodology of mixed method approach was applied and Secondary data was used. The findings of the study shows that the initiatives such as, the AIIB and the NDB are playing a vital role in forging closer diplomatic ties. Furthermore, the BRI project is creating an impact through infrastructure development, people to people goods will, new jobs and tax revenues. It is concluded that as far as China's geo-economic policy towards Central Asia is concerned, regional stability in the short term and energy trade in the long term will be the determining factors.